Salicylic acid and the viral virulence factor 2b regulate the divergent roles of autophagy during cucumber mosaic virus infection. Issue 6 (3rd June 2022) - Shukla, Aayushi; Hoffmann, Gesa; Kushwaha, Nirbhay Kumar; López-González, Silvia; Hofius, Daniel; Hafrén, Anders
ABSTRACT: Macroautophagy/autophagy is a conserved intracellular degradation pathway that has recently emerged as an integral part of plant responses to virus infection. The known mechanisms of autophagy range from the selective degradation of viral components to a more general attenuation of disease symptoms. In addition, several viruses are able to manipulate the autophagy machinery and counteract autophagy-dependent resistance. Despite these findings, the complex interplay of autophagy activities, viral pathogenicity factors, and host defense pathways in disease development remains poorly understood. In the current study, we analyzed the interaction between autophagy and cucumber mosaic virus (CMV) in Arabidopsis thaliana . We show that autophagy is induced during CMV infection and promotes the turnover of the major virulence protein and RNA silencing suppressor 2b. Intriguingly, autophagy induction is mediated by salicylic acid (SA) and dampened by the CMV virulence factor 2b. In accordance with 2b degradation, we found that autophagy provides resistance against CMV by reducing viral RNA accumulation in an RNA silencing-dependent manner. Moreover, autophagy and RNA silencing attenuate while SA promotes CMV disease symptoms, and epistasis analysis suggests that autophagy-dependent disease and resistance are uncoupled. We propose that autophagy counteracts CMV virulence via both 2b degradation and reduced SA-responses, thereby increasing plant fitness with the viral trade-off arising from increased RNA silencing-mediated resistance. Abbreviations: AGO1: argonaute1; ANOVA: analysis of variance; ATG: autophagy related; AZD: AZD8055; CMV: cucumber mosaic virus; CaMV: cauliflower mosaic virus; Co-IP: Co-immunoprecipitation; ConA: concanamycin A; CP: coat protein; DAI: days after inoculation; DCL2/DCL4: dicer like 2/ dicer like 4; DMSO: dimethyl sulfoxide; FLUC: firefly luciferase; GFP: green fluorescent protein; GUS: β-glucuronidase; h: hours; NahG: salicylate hydroxylase; NBR1: neighbor of BRCA1; NPR1: non-expressor of pathogensis related 1; PR1: pathogenesis related 1; RDR6: RNA dependent RNA polymerase 6; RFP: red fluorescent protein; RLUC: renilla luciferase; SA: salicylic acid; SGS3: suppressor of gene silencing 3; TuMV: turnip mosaic virus; WT: wild type